Systems-level host responses to highly and less virulent influenza A (H3N2) virus infections - Fransiskus Xaverius Ivan (2014)
Severe influenza infections have been associated with dysregulated innate immunity that involves macrophages and neutrophils. While the contributions of macrophages to the dysregulation have been broadly investigated, the contributions of neutrophils remain unclear. Hence, in this thesis, we uncovered systems-level neutrophil response to highly virulent influenza infection by employing MPRO neutrophils and highly virulent, mouse adapted H3N2 influenza virus (HVI). Firstly, we showed that HVI induced hypercytokinemia and increased antiviral (interferon) response in the infected lungs. Moreover, increased apoptotic activity and under-expression of genes associated with metabolic and developmental processes mirrored severe pathological changes in HVI-infected lungs. Following pathway analysis, we highlighted the significant roles of the TREM1 signaling pathway in enhancing cytokine expression, and linked the hypercytokinemia to metabolic defect through the activation of LPS/IL1-mediated inhibition of retinoid X receptor (RXR) function pathway. With regards to infection of MPRO neutrophils (optimally containing 20%-30% mature neutrophils, as inspected with differential counting of giemsa-stained cells and flow cytometry based on neutrophil markers), influenza virus could induce apoptosis even though its infection was abortive. Finally, we revealed that HVI mainly activated a rapid induction of type I interferon-inducible genes in MPRO neutrophils, an event that potentially contributes to the dysregulated innate immunity observed in vivo.